2018
DOI: 10.1016/j.ejphar.2018.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Chrysin reverses the depressive-like behavior induced by hypothyroidism in female mice by regulating hippocampal serotonin and dopamine

Abstract: Hypothyroidism is often associated with psychiatric disorders such as depression. In this study, we evaluated the effect of chrysin on depressive-like behavior and monoamine levels in hypothyroid female mice. Hypothyroidism was induced by continuous exposure to 0.1% methimazole (MTZ) in drinking water for 31 days. Exposure to MTZ was associated with low plasma levels of thyroid hormones T3 and T4 compared with the control group. Subsequently, euthyroid and MTZ-induced hypothyroid mice were intragastrically adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…In line with the behavioral results of this study, neurochemicals observation showed that FO significantly decreased the turnover rate of serotonin in the PPD-like rat’s hippocampus, as an increased turnover rate of serotonin has been shown to be associated with high risk of depression [ 40 ]. However, by administering PCPA to PPD rats in this study, the antidepressant-like effects of FO were reversed, as reduction of serotonin was followed by higher immobility time in FST, which indicated higher depressive-like behavior [ 41 ]. In PPD experimental subjects who had involved the hormones fluctuation approach, the concentration of serotonin was affected greatly [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with the behavioral results of this study, neurochemicals observation showed that FO significantly decreased the turnover rate of serotonin in the PPD-like rat’s hippocampus, as an increased turnover rate of serotonin has been shown to be associated with high risk of depression [ 40 ]. However, by administering PCPA to PPD rats in this study, the antidepressant-like effects of FO were reversed, as reduction of serotonin was followed by higher immobility time in FST, which indicated higher depressive-like behavior [ 41 ]. In PPD experimental subjects who had involved the hormones fluctuation approach, the concentration of serotonin was affected greatly [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chrysin was shown to reduce dopamine depletion and protect against the neurodegeneration of dopaminergic neurons of the brain [61,65]. It was also observed that chrysin treatment can significantly induce dopamine level recovery in the hippocampus and the prefrontal cortex region of the brain [66].…”
Section: Chrysin As a Mao Inhibitormentioning
confidence: 97%
“…Noradrenaline content was not altered by treatments. Therefore, chrysin treatment reverses depressive-like behaviors in hypothyroid female mice and proposing the involvement of 5HT and dopamine in these effects [17].…”
Section: Anxiolytic and Anti-depressant Effectmentioning
confidence: 98%